Intravenous Oxytocin Vs Vaginal Prostaglandin E2 for Inducing Labour in Prelabor Rupture of Membranes at Term - Syeda Sana Ali, Lubna Aslam, Fareen Memon, Sajida Imran, Ayesha Inayat, Hifsa Naseem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: In patients with prelabor membrane rupture at term, evaluate the relative effectiveness of vaginal prostaglandin E2 and oxytocin infusion for induction of labour. Study design: Randomized clinical trial Place and Duration: This study was conducted in the multi centers at the Department of Obstetrics and Gynaecology, Murshid Hospital and Health Care Center Karachi, Sindh and PGMI/AMC/LGH Lahore, Punjab in the period from March, 2022 to August, 2022. Material and methods: Ninety patients with term membrane rupture who were brought through emergency for induction of labour were randomly assigned to either group I (oxytocin) or group II (vaginal prostaglandin E2) and monitored until delivery. We recorded the number of vaginal births that occurred within 24 hours of the induction of labour and the time it took for labour to begin after the induction. All of the data was analyzed with SPSS 23.0. Results: Mean age of the patients in group I was 26.5±6.26 years and in group II mean age was 24.7±5.60. Mean BMI in group I was 25.1±8.16 kg/m2 and in group II mean BMI was 26.1±7.36 kg/m2. Those who were induced with intravenous oxytocin had 22 (48.9%) vaginal deliveries within 24 hours, while patients who were induced with vaginal PGE2 had 32 (71%) vaginal deliveries within 24 hours. Conclusion: The findings of this study led us to the conclusion that vaginally administered PGE2 causes more patients to deliver their babies vaginally within twenty-four hours. Keywords: Oxytocin, Induction of labor, Rupture of membranes, PGE2